Menakar Sosiologi Dakwah dan Moderasi Beragama di Indonesia: Measuring the Sociology of Da'wah and Religious Moderation in Indonesia - Mustamin, Chanra; Mahmuddin (Litera Academica Publishing, 2025)
This research aims to analyze the meaning of modernization and how this concept influences the context of da'wah and religious life in Indonesia. Apart from that, this research also aims to understand the concept of multicultural moderation in a pluralistic Indonesian society. This research uses a qualitative approach with a descriptive-analytical design. The research results show that the Indonesian nation is a diverse nation in terms of ethnicity, language, culture and religion. Even though Muslims are the majority in Indonesia, this country is not an Islamic country and does not implement Islamic law in its state system. Indonesia is the Unitary State of the Republic of Indonesia (NKRI) which is based on Pancasila and the 1945 Constitution. The challenge in current da'wah scholarship is to find new formulas that suit the diversity of traditions, cultures and religions in Indonesia. Therefore, a typical Indonesian da'wah model approach is needed which is a response to multiculturalism. Religious moderation itself is a moderate way of viewing religion, namely understanding and practicing religious teachings without extremism, both to the right and to the left. In this context, strengthening knowledge and understanding of national insight is very necessary, especially for state servants and other parties who have an interest in managing the country.